Nurses’ Knowledge Regarding FoodDrug Interaction in the Intensive Care and Emergency Hospitals - Lafi, Samir Y; Kamali, Aram Salih Mohammed Amin; Sharif, Bayan Omar (Kurdistan Journal of Applied Research, 2019)
Usually supplement is essential and fundamental components for ensure and creating the human body, also drugs seem to survey the life of each individual and ensure the wellbeing for a long life aimed most of illness, but in case nourishment sedate interaction ignored since of information shortage almost it or any reason maybe lead to futile of medicine for the patients or cause life threatening condition because of that, one of the most significant ethical point in every health care setting in the world is patient's safety; and the care for patients must be improved in every country to prevent complication of interaction between food and drug. The main objective of this cross-sectional study has been conducted to assess the nurses' knowledge regarding food-drug interaction (FDI) at the intensive care in both of Shar and emergency hospitals in the Slemani city, the data were collected during the period of October up to the end of December. Non-probability, (purposive sample) of 78 nurses at both hospitals, a questionnaire was designed according to literatures and books regarding FDI which contained 25 items, 8 items for demographic characteristics, and 17 items concerning FDI. The validity of the questionnaire was given to a panel of 7 experts, a pilot study was carried out to check the reliability of the questionnaire which determined through the use of stability reliability (test-retest) approach which was estimated as r = 0.81. The data were collected through the interviewing of the study sample and analyzed through the using of the Statistical Package for Social Sciences SPSS, version 23, and analyzed through the application of descriptive and inferential statistical analysis. The findings of the present study conclude that more than half of nurses had low knowledge and none of them had high level of knowledge, also there is no significant association between the levels of knowledge with age, gender, educational level, years of experience and working place. The study suggested extends the knowledge of nurses regarding the FDI, by training courses from clinical pharmacologists.